Deletion of calcineurin from astrocytes reproduces proteome signature of Alzheimer's disease and epilepsy and predisposes to seizures. (December 2021) - Tapella, Laura; Dematteis, Giulia; Ruffinatti, Federico Alessandro; Ponzoni, Luisa; Fiordaliso, Fabio; Corbelli, Alessandro; Albanese, Enrico; Pistolato, Beatrice; Pagano, Jessica; Barberis, Elettra; Marengo, Emilio; Balducci, Claudia; et al.
Highlights: Astroglial calcineurin KO (ACN-KO) mice, at 1 mo, show alterations of protein expression at posttranscriptional level. Bioinformatic analysis links ACN-KO proteomics to Alzheimer's disease and epilepsy. In Barnes maze ACN-KO mice use serial search strategy. From 5 month of age ACN-KO mice show increased risk to develop epileptic seizures. Abstract: Calcineurin (CaN), acting downstream of intracellular calcium signals, orchestrates cellular remodeling in many cellular types. In astrocytes, major homeostatic players in the central nervous system (CNS), CaN is involved in neuroinflammation and gliosis, while its role in healthy CNS or in early neuro-pathogenesis is poorly understood. Here we report that in mice with conditional deletion of CaN in GFAP-expressing astrocytes (astroglial calcineurin KO, ACN-KO), at 1 month of age, transcription was largely unchanged, while the proteome was deranged in the hippocampus and cerebellum. Gene ontology analysis revealed overrepresentation of annotations related to myelin sheath, mitochondria, ribosome and cytoskeleton. Over-represented pathways were related to protein synthesis, oxidative phosphorylation, mTOR and neurological disorders, including Alzheimer's disease (AD) and seizure disorder. Comparison with published proteomic datasets showed significant overlap with the proteome of a familial AD mouse model and of human subjects with drug-resistant seizures. ACN-KO mice showed no alterations of motor activity, equilibrium, anxiety or depressive state. However, in Barnes maze ACN-KO mice learned the task but adopted serial search strategy. Strikingly, beginning from about 5 months of age ACN-KO mice developed spontaneous tonic-clonic seizures with an inflammatory signature of epileptic brains. Altogether, our data suggest that the deletion of astroglial CaN produces features of neurological disorders and predisposes mice to seizures. We suggest that calcineurin in astrocytes may serve as a novel Ca 2+ -sensitive switch which regulates protein expression and homeostasis in the central nervous system. Graphical Abstract: Image, graphical abstract